THERABAND® CLX gold reduces knee-width index and range of motion during overhead, barbell squatting. Issue 2 (17th February 2021) - Forman, Davis A.; Forman, Garrick N.; Button, Duane C.; Holmes, Michael W.R.
ABSTRACT: This study examined the influence of the Theraband TM CLX gold band on lower-limb muscle activity and kinematics during an overhead barbell squat. Participants performed two sets (band and no-band) of 12 repetitions of overhead barbell squats at 25% bodyweight. Three-dimensional kinematics were measured using motion capture with rigid bodies placed bilaterally on the foot, shank, thigh and thorax. Electromyography was collected from seven, bilateral muscles of the lower-limb and was unchanged for all muscles between conditions. Medial knee collapse was calculated using a knee-width index (KWI) ratio of the distance between the lateral epicondyles of the femur and the lateral malleoli. Average KWI was smaller during the band condition for the concentric (No band: 0.99 ± 0.05, Band: 0.97 ± 0.06, p < 0.05) and eccentric phases (No band: 1.00 ± 0.06, Band: 0.97 ± 0.05, p < 0.05). KWI was significantly smaller with the use of the Theraband TM CLX. As the gold band is the strongest of the CLX offerings, any benefit of increased proprioception may have been lost due to the high resistance of the band. Further research examining the dose-response of elastic band resistance to knee alignment may be needed to inform proper exercise prescription.